Windows Vista in a nutshell - Gralla, Preston (In a nutshell., 2006)
'Windows Vista in a Nutshell' documents everything there is to know about the newest version of the world's most widely used operating system. This desktop reference is dedicated to making the computer safer, easier and more fun.